Esеmсiitova Z.B., Sinyavsky Yu.A., Umutbaeva G.B., Yakunin A.V. The Inﬂuence of Hypokinesia on the Status of the Antioxidant defense System in Blood and Tissues of Rats: 1Al-Farabi Kazakh National university, Kazakhstan, Almaty 2Kazakh Academy of Nutrition, Kazakhstan, Almaty (Eurasian Journal of Ecology, 2018)
The results of biochemical studies of the effect of hypokinetic stresson the state of antioxidant defense system in the blood and liver of rats,as well as the correction of the effects of antioxidant substances hypokinesia nature – alpha-tocopherol, and resveratrol. Assessing the impactof hypokinesia on the state of the antioxidant status of the animals wascarried out on white rats weighing 250 ± 50g. The serum and liver wereevaluated postmitochondrial supernatant protein, superoxide dismutaseactivity (SOD) and catalase, the level of final and intermediate products oflipid peroxidation and total antioxidant activity. Evaluation of primary lipidperoxidation products (diene conjugates), the secondary lipid peroxidationproducts (malondialdehyde) and the end of lipid peroxidation products(Schiff base) testified to improve their level in the dynamics of 15 and 30days of hypokinesia, marked decrease in activity of antioxidant enzymes.The additional intake of resveratrol and alpha-tocopherol favorable impacton the state of the antioxidant system, which was manifested in a significant decrease in serum and liver of rats lipid peroxidation products andincreasing the total antioxidant activity.Key words: antioxidant protection, alpha tokofrol, hypokinesia, human ecology, lipid peroxidation, LPO produky, resveratrol.